The Use of Copper Slag in the Thermolysis Process for Solar Hydrogen Production—A Novel Alternative for the Circular Economy - Manuel Fuentes; Susana Leiva-Guajardo; Atul Sagade; Felipe Sepúlveda; Alvaro Soliz; Norman Toro; José Ángel Cobos Murcia; V. E. Reyes Cruz; Mario Toledo; Edward Fuentealba; Felipe M. Galleguillos Madrid (Applied Sciences)
Copper slag, produced in pyrometallurgical processes, has the potential to generate hydrogen through thermolysis, depending on its composition. This manuscript explores the use of copper slag as a highly abundant and low-cost material for thermochemical water splitting using concentrated solar power. Copper slag can undergo endothermic reactions with water vapor at high temperatures, conditions which are favorable for activating hydrogen evolution reactions which can be a potential resource for metal recovery such as magnetite and hematite in the circular economy. While research on copper slag and its components has primarily focused on the recovery of valuable metals and material reuse, its direct application in hydrogen production remains largely unexplored, partly due to historically low interest in hydrogen as an energy source. The vast deposits of copper slag in the Atacama Desert, combined with the growing demand for renewable energy, present a unique opportunity to develop sustainable and cost-effective hydrogen production technologies.